Manajemen Program Unggulan dalam Meningkatkan Kualitas Pendidikan di SMP Muhammadiyah 7 Yogyakarta - Kartiningsih, Sri; Mulyono, Rahmat; Rejokirono, Rejokirono (Media Manajemen Pendidikan, 2025)
The purposes of this study are to analyze: (1) the practice of excellent program management at SMP Muhammadiyah 7 Yogyakarta. (2) the achievement of improving the quality of education at SMP Muhammadiyah 7 Yogyakarta. This study was a qualitative research which uses interview, observation, and documentation techniques. Data were analyzed using the Miles and Huberman model including data collection, reduction, data presentation, and drawing conclusions. Based on the results of the data analysis, the following conclusions were obtained: (1) Planning includes the stages of formulating objectives, formulating policies and budget planning; (2) Organizing consists of activities providing employees, dividing work, determining authority, training employees, and socializing programs; (3) Implementation includes the realization of the activities of the flagship program including Tahfidz, ICT, Arts and Culture and KKO in which consists of three sports branches: volleyball, badminton and football; and (4) Supervision includes determining standards, evaluation, corrective actions, and follow-up. Improving the quality of education at SMP Muhammadiyah 7 Yogyakarta through optimizing human resources is one of the processes of improving the quality of education through flagship programs at SMP Muhammadiyah 7 Yogyakarta. The potential of existing human resources is optimized by becoming trainers in flagship programs.